(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
This paper focuses on the intersections between the constructed female sexual and gender identity and the spatial identity, specifically the regional Balkan identity of the female protagonists of the selected novels by the intersectional feminist approach. These are novels by contemporary women writers from the post-Yugoslav space, published in the period from 2008 to 2011, are: Korov je samo biljka na krivom mjestu (Weed is only a plant in the wrong place) by Stela Jelinčić (2008), Paprat (Fern) by Dunja Radosavljević (2009) and Mogla je biti prosta priča (It could have been a simple story) by Ajla Terzić (2011). The selected novels, which focus on issues of female subjectivity and narrate the experiences of women in the post-Yugoslav transition context from a female perspective, are analysed from a gender-oriented and regionally specific perspective. Of particular importance for the analysis are the premises of intersectional feminism and contemporary feminist theories, especially the “locational feminist criticism” and feminist discourses within the “new geography of identity” by Susan Stanford Friedman, which are combined with the critique of Balkanist discourse by Maria Todorova and applied to the analysis of the novels. In this context, the key is the imagology of the Balkans as an imagined and constructed space in contrast to the so-called Western imagination of space. Likewise, an attempt is made to map and examine the aspects that offer the possibility of questioning sexual, gender and spatial identities as social constructs as well as the discourses that determine the socially-constructed notions of femininity and the ways in which this problem is manifested in the literary production of contemporary female authors from the postYugoslav space at the beginning of the 21st century. Furthermore, the paper takes into consideration the issues and constructions of female protagonists as migrant and displaced female subjects, who either find themselves in an ambivalent position between, between spaces and cultures, or are opting for multiple affiliations.